Reflection seismic study of the post-glacial Burträsk fault: Shot gathers with geometry ... : Reflexionsseismiska mätningar över Burträsk-förkastningen: Shot gathers med geometri ... - Juhlin, Christopher; Lund, Björn (Uppsala University, 2019)
In 2008, a 22 km long high resolution reflection seismic profile was acquired over the Burträsk fault in Northern Sweden. The Burträsk fault formed at the end of the last glacial, triggered by the rapid melting of the Scandinavian ice sheet and the following crustal rebound. The aim of the survey was to image the structure of the fault with depth. The profile followed existing roads resulting in a very crooked acquisition geometry. A list of the key acquisition parameters is given below. The dataset was first processed and published in 2011. In 2018, the dataset was reprocessed using an additional cross-dip correction step to improve the imaging of reflection with a dip component in the cross-profile direction. The following data files are available for downloading: 1) raw shot gathers (decoded and quality controlled, with geometry information in the headers) 2) original stacked section from Juhlin and Lund (2011) 3) cross-dip corrected stacked section from Beckel and Juhlin (2019) 4) cross-dip corrected ... : Reflexionsseismiska mätningar över Burträsk-förkastningen I norra Sverige År 2008 gjordes en reflexionsseismiska undersökning över Burträsk-förkastningen I norra Sverige. Förkastningen formades vid slutet av sista istiden när glaciärerna nedsmältade snabbt. Ändamålen av undersökningen var att avbilda förkastningens djupa strukturerna. Seismisk profilen följde befintliga vägar, vilket resulterade I en ganska slingrig geometri av profilen. Datasetet bearbetades och publicerades först av Juhlin & Lund (2011). I 2018 gjordes ett nytt bearbetning av som omfattade en ytterligare steg för att korrigera effekten av 3D profilgeometrin (Beckel & Juhlin, 2019). En mer detaljerad beskrivning av datasetet som inkluderar alla viktiga parametrar är tillgängligt på den engelska katalogsidan:https://snd.gu.se/en/catalogue/study/SND1099 Utförlig beskrivning av datasetet finns på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1099 För tillgång till data kontakta request@snd.gu.se eller använd ...